2001
DOI: 10.1177/000331970105200301
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Primary Angioplasty with Stent Implantation and Thrombolysis in Restoring Basal Coronary Artery Flow in Acute ST Segment Elevation Myocardial Infarction: Quantitative Assessment Using the Corrected TIMI Frame Count

Abstract: Following thrombolysis and primary percutaneous transluminal coronary angioplasty (PTCA) for acute ST segment elevation myocardial infarction, basal flow in the culprit artery is known to influence prognosis. The purpose of this study was to determine if differences exist in basal flow in culprit and nonculprit coronary arteries in patients with acute ST segment elevation myocardial infarction who were treated with thrombolysis or primary PTCA with stent implantation. Twenty patients were randomized to thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Third, any correlation between TFC and 2/3D parameters was investigated, examining STEMI and NSTEMI subgroups separately. As a cut-off for TFC changes, ≥3 vs. <3 groups were compared based on previous studies investigating the significance level on the number of frame change [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Third, any correlation between TFC and 2/3D parameters was investigated, examining STEMI and NSTEMI subgroups separately. As a cut-off for TFC changes, ≥3 vs. <3 groups were compared based on previous studies investigating the significance level on the number of frame change [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it has been shown that the time to reperfusion after lytic failure influences both procedural success and in-hospital results with the best outcomes obtained when this period is less than 8 h [27,28]. Furthermore, recent trials have demonstrated that rescue percutaneous coronary angioplasty (PTCA) early after failed thrombolysis seems to be as effective and safe as primary PTCA [29][30][31][32][33]. Thus, a policy aimed at performing rescue PCI to restore normal coronary flow as soon as thrombolysis fails appears to be warranted.…”
Section: Time Window For Rescue Pcimentioning
confidence: 99%
“…Others have examined the effect of time of day on outcome in PCI, and found no effect. 86,87 Studies have suggested that the mortality after PCI is unchanged if the procedure is delayed by up to 6 hours, 88,89 although this may not hold for highrisk patients. The NSF for coronary heart disease aims for a standard of 60 minutes between calling for professional help and thrombolysis (Standard six).…”
Section: Immediate Angioplasty Versus Community Thrombolysismentioning
confidence: 99%